KNOWLEDGE, TRAINING AND AGING - Saiz, Carlos (Anales de Psicología / Annals of Psychology)
The goal of this article is to analyse the possibility of stopping or slowing down the deterioration of the intellectual performance with the aging process. To solve this problem I have studied the process of acquiring knowledge and that of the cognitive changes, in order to examine the role of instructional training in old age. Many studies have showed that with practice and training this intellectual deterioration associated with aging can be slowed. Taking into account the data, the nature of cognitive change, and the learning process, I have analysed several training programs. These programs aim to improve the problem solving capacity through various methods. Using several programs improves the intellectual activitiy and obtains a better personal welfare.